Survei Pengetahuan Orang Tua melalui Kegiatan Sekolah Keluarga Balita (SKB) dengan Online Learning: Parental Knowledge Survey through Toddler Family School Activities (SKB) with Online Learning - Ari Indra Susanti; Dani Ferdian; Eka Noyan Nur Annisa; Raya Faiha Calista (Jurnal Bidan Cerdas, 2020)
Health education in the digital era requires one social media, namely WhatsApp as an information media that is considered effective and efficient. Thus, parents get health education through WhatsApp in the Sekolah Keluarga Balita (SKB) online learning activities with the agreed time. This study aims to determine the knowledge of parents about the First 1000 Days of Life (HPK) through the SKB online learning that used WhatsApp. The research method used description with a cross-sectional approach. This research was conducted in March 2020 among parents of toddlers living in the fostered villages of Kampung Bestari Astra (KBA) as many as 150 people. The sampling technique was used accidental sampling. This questionnaire was given to the respondent in the form of bit.ly/ (google form). This questionnaire was filled out by respondents before being given a health education video. Data analysis using univariate have presented in the form of a frequency distribution table. The results showed that most participants in the Joint Decree were 135 people, with the age of 20-35 years as many as 60 people, and 78 parents were unfavorable knowledge. The conclusion in this study that some parents aged 20-35 years have less knowledge about the First 1000 Days of Life (HPK) so that health education is needed in a Toddler Family School (SKB) online using WhatsApp.